THE EFFECTIVENESS USING ENGLISH SONG IN TEACHING ENGLISH VOCABUALRY OF THE EIGHTH GRADE STUDENTS OF SMPN 2 NAMBAI-NAMPI DISTRICT, PAPUA - Matius Pakiding (Teaching English as a Foreign Language Overseas Journal, 2016)
The objective of this research to find out whether using English song is effective usedin teaching English Vocabulary of the eighth grade students of SMPN 2 Nambai-Nampi District, Papua.This research used experimental method. The population of study was of the eighthgrade in SMPN 2 Nambai-Nampi District, Papua. It consists of 20 students,therefore the researcher took 20 students as sample. The data collected through writtentest through pre-test –treatment, and post-test for field researchThe result of comparison between students’ score in pre-test and post-test indicatedthat there was a significant difference the mean score of pre-test was 51,75 and themean score of post-test was 69. The increasing of the mean score of post-test indicatesthat using English song is effective in teaching vocabulary to the eighth grade studentsof SMPN 2 Nambai-Nampi District, Papua..Based on the t-test analysis that t-score (6,24) was higher than t-table (1,729), it meansthat H1 was accepted, it can be concluded that the used of English song is effective inteaching vocabulary the eighth grade students of SMPN 2 Nambai-Nampi District,Papua.